Celebrating forum @ forty - Kral, Thomas J. (Philippine Journal of Linguistics, 2003)
The prototype for what we know as the "English Teaching Forum" was a newsletter published by the Information Center Service of the United States Information Agency in 1962. The overwhelming positive response to the newsletter indicated worldwide support for the publication, and it has continued as a journal for teachers of English overseas for four decades. At its peak during the mid-1990s, the "English Teaching Forum" had a circulation of 120, 000. The "Forum" has offered the opportunity to many teachers for publishing their first article; and it has attracted manuscripts from such noted specialists as Mary Finocchiaro, Marianne Celce-Murcia, Larry Smith, Mario Rinvolucci, and others. Conceived as a journal providing practical ideas for classroom teaching, curriculum development and materials writing, the "Forum" is not the vehicle for people to publish chapters from their master's theses or dissertations. The typical article may begin with theory or a short description of an action research project, but it will then focus on applications useful to other teachers and program developers. Though the Forum has modified its format and added an on-line option, it continues to encourage the active exchange of ideas and experiences of teachers of English worldwide. This talk will look at how teachers can use the "Forum" in training both teachers and trainers of teachers. While the "Forum" provides a historical narrative of the practical tool for meeting present-day challenges.